PENDETEKSIAN SEL DARAH PUTIH DARI CITRA PREPARAT DENGAN YOU ONLY LOOK ONCE - Fredriek Andrianson; Lina Lina; Arlends Chris (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
Blood is a fluid that in the body, in the blood there are platelets, red blood cells and white blood cells. White blood cells play an important role in maintaining the body's defense from viruses or bacteria. Many diseases are related to white blood cells, to find out these conditions you need to do an examination to identify white blood cells. Based on this, this design aims to detect white blood cells on images of blood preparations. The method used is You Only Look Once to detect white blood cells in images of blood preparations. The test results showed that the proposed method obtained an accuracy rate of 100% for the detection of white blood cells with stained images and white blood cells without stained images obtained an accuracy rate of 76.5%.